Comments on “New Structural Economics” by Justin Yifu Lin - Rodrik, Dani (World Bank, 2013)
"Justin Lin wants to make structuralist economics respectable again, and I applaud him for that. He wants to marry structuralism with neoclassical economic reasoning, and I applaud this idea too. So he has two cheers from me. I withhold my third cheer so I can quibble with some of what he writes.